Prevalence and molecular typing of Clostridium perfringens in captive wildlife in India. (April 2017) - Milton, Arockiasamy Arun Prince; Agarwal, Rajesh Kumar; Bhuvana Priya, Govindarajan; Saminathan, Mani; Aravind, Manivasagam; Reddy, Avinash; Athira, C.K.; Ramees, Thadiyampuram; Sharma, Anil Kumar; Kumar, Ashok
Abstract: The prevalence of Clostridium perfringens in captive wildlife in India has not been reported. The objective of the study was to determine the fecal prevalence of C. perfringens in captive wildlife in India. The prevalence in captive wild ruminants, non-ruminants, birds and caretakers were 34.1%, 36%, 22.5% and 6.7%, respectively. Toxinotyping of C. perfringens indicated that the predominant type was type A with a prevalence rate of 69.7%, followed by type A with cpb2 gene (28.3%) and type B (2.%).